REFORMULATE COMPANY BUSINESS STRATEGY TO MAINTAIN COMPETITIVE ADVANTAGE: CASE STUDY PT GALAMEDIA - Muttaqin, Rizqi P; Alam, Gilang Nur; Saputera, Denny (CENTRAL ASIA AND THE CAUCASUS, 2022)
Increasingly rapid technological developments affecting the performance of PT Galamedia with indicator rates of profit declining. To survive in this situation Galamedia launches digital products that are expected to develop and survive to compete in the next few years. But in its implementation Galamedia cannot operate its digital business perfectly so that the development of its digital business performance is not in line with the decline in traditional business performance. Therefore, to seek and maximize the performance of its digital business, it is necessary to change the system and organizational structure within Galamedia.In this Research, first conducted a SWOT analysis, and GE TOWS matrix to evaluate the condition Galamedia of various factors, after finding the results of the analysis determined the strategic direction to be taken by Galamedia. The results of the analysis show that Galamedia has horizontal integration with the growth strategy. The strategy is designed to determine the new vision and mission of Galamedia using the Strategy Map from David P Norton and Robert S Kaplan coupled with the 7S framework from McKinsey. After the new vision and mission was designed from the Strategy Map then developed the Balanced Scorecard from the same book to design implementation. The results of the designed implementation are planned to be executed using Kotter 8 Steps Accelerator with guidance on change management, because the main strategy is to changes so that the changes implemented can be managed properly by Galamedia.The results of this study indicate that Galamedia must develop the business with the birth of two alternatives from the Strategy Map concept which is designed to issue new products or cooperate with other companies, in this case for Galamedia the possibility of both strategy could be conducted by collaborating with InfoBandung an new digital media company to create new products and share the knowledge between each other or excellencing the research and development part in digital products to replicate or even create new product similar to InfoBandung.